A survey of deep learning based modulation recognition - Shujun SUN; Shengliang PENG; Yudong YAO; Xi YANG (Dianxin kexue)
Modulation recognition is one of the fundamental tasks for communications systems, which can be widely applied in various fields, such as cognitive radio, intelligent communications, radio surveillance, electronic warfare, etc.In recent years, deep learning (DL) based modulation recognition has attracted great attention due to its superiority in feature extraction and recognition performance.The techniques of DL based modulation recognition were systematically summarized.Firstly, some knowledge relevant to DL based modulation recognition was introduced.Then, the system architecture, data pre-processing methods, deep neural network structures, prevalent datasets and performance metrics of DL based modulation recognition were illustrated.Finally, the future directions of DL based modulation recognition were also discussed.